2015
DOI: 10.1002/pola.27889
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic β‐cyclodextrin‐based star‐like block copolymer unimolecular micelles for facile in situ preparation of gold nanoparticles

Abstract: Multifunctional polymer unimolecular micelles, which are used as templates to fabricate stable gold nanoparticles (GNPs) in one‐step without external reductant, have been designed and prepared. Amphiphilic 21‐arm star‐like block copolymers β‐cyclodextrin‐{poly(lactide)‐poly(2‐(dimethylamino) ethyl methacrylate)‐poly[oligo(2‐ethyl‐2‐oxazoline)methacrylate]}21 [β‐CD‐(PLA‐PDMAEMA‐PEtOxMA)21] and the precursors are synthesized by the combination of ring‐opening polymerization (ROP) and activators regenerated by el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 40 publications
(40 reference statements)
0
42
0
Order By: Relevance
“…2-(Dimethylamino)ethyl methacrylate (DMAEMA, >98%, TCI, Tokyo, Japan) was purified by passing through a column filled with neutral alumina to remove inhibitor before use. Oligo(2-ethyl-2-oxazoline)methacrylate (EtOxMA) has been synthesized and reported in our previous article [32]. Triethylamine (TEA, 99%, Sigma-Aldrich, St. Louis, MO, USA), toluene (Sigma-Aldrich), tetrahydrofuran (THF, Sinopharm, Beijing, China), and anisole (Sinopharm) were dried over CaH 2 and distilled under nitrogen.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2-(Dimethylamino)ethyl methacrylate (DMAEMA, >98%, TCI, Tokyo, Japan) was purified by passing through a column filled with neutral alumina to remove inhibitor before use. Oligo(2-ethyl-2-oxazoline)methacrylate (EtOxMA) has been synthesized and reported in our previous article [32]. Triethylamine (TEA, 99%, Sigma-Aldrich, St. Louis, MO, USA), toluene (Sigma-Aldrich), tetrahydrofuran (THF, Sinopharm, Beijing, China), and anisole (Sinopharm) were dried over CaH 2 and distilled under nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…Dulbecco's modified Eagle medium (DMEM), fetal bovine serum (FBS), penicillin, and streptomycin were all purchased from Invitrogen (Carlsbad, CA, USA). 21 The amphiphilic pH-responsive star copolymer was synthesized by combining activator regenerated by electron-transfer atom-transfer radical polymerization (ARGET ATRP) with ring opening polymerization (ROP) [32]. First, the synthesis of β-CD-(PLA-OH) 21 by ROP of D,L-LA (5.50 g, 37.8 mmol) in anhydrous toluene (25 mL) was carried out using β-CD (681 mg, 0.6 mmol) as an initiator and Sn(Oct) 2 (65 µL, 0.2 mmol) as a catalyst at 130 • C for 24 h. The macroinitiator β-CD-(PLA-Br) 21 was then synthesized from β-CD-(PLA-OH) 21 (5.50 g, 0.6 mmol) and TEA (3.34 mL, 24 mmol) with 2-bromoisobutyryl bromide (2.97 mL, 24 mmol) in anhydrous THF (100 mL) at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some reports have demonstrated that PDMAEMA can act as both reducing agent and stabilizer simultaneously in the formation of gold nanoparticles, [21][22][23][24] based on the fact that Poly (2-(dimethylamino) ethyl methacrylate) (PDMAEMA) is a hydrophilic polymer with temperature and pH sensitivities, excellent biocompatibility, and a well-studied environmentally responsive polymer. 25 Such an approach greatly simplified the preparation and purification of gold nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] In particular, pH-responsive polymeric micelles are selfassembled by triblock or multi-block copolymers containing hydrophilic blocks, hydrophobic blocks and functional response blocks. A substantial proportion of hydrophilic/ hydrophobic block in the micelles structure improved the in vivo micelle stability and drug-loading capability but at the price of the reduced micellar pH responsiveness.…”
Section: Introductionmentioning
confidence: 99%